University Knowledge Management: proposal for broaden integrative perspective - Ayodele, Freida Ozavize; Yao, Liu; Hasnah, Haron (World Scientific Publishing Co Pte Ltd, 2018)
The study gives an overview and critique and identifies literature on university knowledge management (KM) research to ascertain gaps for further investigation. A systematic search of articles about university KM research in the Web of Science and Scopus was scrutinised using pre-defined criteria. After screening, 46 articles that met the selection criteria were reviewed. Findings revealed that the academic aspects are over-explored with some KM themes, whereas the non-academic university KM is under-explored. Moreover, the reviewed literature showed that the university KM cut across significant countries of the world with a large concentration of the research articles in USA, UK, and Malaysia. The study proffered ways of advancing university KM research agenda in the future by considering the under-explored contexts for more meaningful contributions to KM practice and theory development.